What would your party colleagues Say? Carlos’ homosexuality in My Tender Matador by Pedro Lemebel - Nuñez, Silvana (Nomadías, 2025)
In this article, I will explore Carlos’ sexuality from the book My Tender Matador by Pedro Lemebel (2001) where the character is presented as a member of the Manuel Rodríguez Patriotic Front (FPMR) who becomes involved with Loca del Frente, a queer old woman, who for affection towards Carlos ends up doing favors to him that end up involving her in the political plans of the young guerrilla. This will be addressed through Carlos’ masculinity and sexuality. This will be adressed trough the masculinity based on the contrast between Carlos has with Loca del Frente. And finally, to reflect on his homosexuality we will see how the figure of the new man and his participation in the guerrilla is conflicted by his militancy as an space of oppression for his identity.